2009
DOI: 10.1016/j.jcmg.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Targeted Gene Delivery Induces Angiogenesis After a Myocardial Infarction in Mice

Abstract: Noninvasive UTMD successfully delivered VEGF and SCF genes into the infarcted heart, increased vascular density, and improved myocardial perfusion and ventricular function. The UTMD technique may be an ideal method for noninvasive, repeated gene delivery after an MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 25 publications
3
104
0
Order By: Relevance
“…[26][27][28] Possible answers to this problem have been tested, such as a combination of several different VEGF-isoforms 5 or suppression of endothelial inflammation in atherosclerotic arteries to enhance the effects of VEGF. 29 In addition, ultrasound has been used at the gene delivery site during gene transfer to enhance angiogenesis, 30 and use of angiogenetic growth factors in combination with stem cells has also shown promising results. 31 In conclusion, our results suggest that local, intravascular VEGF-GT is safe and well tolerated over long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Possible answers to this problem have been tested, such as a combination of several different VEGF-isoforms 5 or suppression of endothelial inflammation in atherosclerotic arteries to enhance the effects of VEGF. 29 In addition, ultrasound has been used at the gene delivery site during gene transfer to enhance angiogenesis, 30 and use of angiogenetic growth factors in combination with stem cells has also shown promising results. 31 In conclusion, our results suggest that local, intravascular VEGF-GT is safe and well tolerated over long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Additional data included direct measurement of protein expression within the myocardium. The results indicated that the ultrasounddirected microbubble gene combination therapy efficiently delivered both stem cell factor and VEGF to the infarcted heart muscle, resulting in an increased expression of the specified genes associated with increased vascular density derived from VEGF; myocardial perfusion and ventricular function were notably improved, consistent with therapeutic efficacy (21).…”
mentioning
confidence: 69%
“…Similar research protocols using gene therapy have been performed in the domain of cardiovascular disease (21,50,64). Shohet et al (50) implemented ultrasound-mediated gene delivery to achieve a 10-fold increase in protein expression of the myocardium compared with controls.…”
mentioning
confidence: 99%
“…27 Other studies evaluated the capacity of ultrasound-targeted microbubble destruction to deliver viral vectors successfully delivering VEGF and SCF genes into the infarcted heart in mice. 28 Moreover, access can be realized by a special catheter that is advanced into the coronary sinus and target either the myocardium or coronary artery. A composite catheter system (TransAccess, TransVascular Inc., Menlo Park, CA, USA) incorporates a phased-array ultrasound tip for guidance and carries a sheathed, extendable nitinol needle.…”
Section: Percutaneous Methods Of Vector Delivery D Ladage Et Almentioning
confidence: 99%